Analisis Pengaruh Penanganan Keluhan dan Kepuasan Konsumen terhadap Loyalitas Konsumen Sim Card Telkomsel pada Masyarakat Kota Surakarta - Muhammad Agung Adi Nugroho; Ihwan Susila (BADAN PENERBIT STIEPARI PRESS, 2026)
The purpose of this research is to analyze and test the mediating role of customer satisfaction on Telkomsel sim card consumer loyalty. This research uses a survey method by distributing questionnaires to 145 Telkomsel sim card users in the Surakarta area and analyzing the data using respondent filter analysis, descriptive statistical analysis, and Structural Equation Modeling (SEM) analysis. The findings in this research show that complaint handling has an influence on consumer loyalty, while customer satisfaction also influences the level of consumer loyalty. Consumer satisfaction is influenced by the level of handling of consumers by the Telkomsel SIM card provider. Furthermore, consumer satisfaction is proven to mediate the influence of complaint handling on Telkomsel SIM card consumer loyalty in the people of Surakarta. These findings provide a theoretical basis for Telkomsel Providers to pay attention to complaint handling and consumer satisfaction in increasing Telkomsel SIM Card consumer loyalty.